AKIBAT HUKUM PENYELENGGARAAN KONSER MUSIK TANPA LISENSI TERHADAP PEMBAYARAN ROYALTI HAK CIPTA - Dhani Ari Sanjaya; Emilda Kuspraningrum; Grizelda Grizelda (Jurnal Ilmiah Advokasi, 2026)
This copyright provides protection to creators, ensuring that they have exclusive control over the production, distribution, and presentation of their work, as well as obtaining fair royalties for the effort and creativity they have put in. This study uses a type of socio legal research approach to examine the implementation of regulations on the withdrawal of royalties for song/music users in the implementation of music concerts that are not bound by license agreements in Samarinda City and to examine the effectiveness of receiving royalties from copyright holders in the implementation of music concerts that are not bound by license agreements in Samarinda City. Based on the results of the study, it is known that first, the implementation of regulations related to the royalty withdrawamechanism regulated in Government Regulation Number 56 of 2021 concerning the Management of Song/Music Copyright Royalties, in practice in Samarinda City has not run as expected by this regulation. Second, public awareness of the obligation to pay royalties is quite good, but only the mechanism for receiving royalties is different. The public, especially song/music users and copyright holders, runs a mechanism that is considered more effective, efficient, and on target and the royalty results can be felt directly by the creator and/or copyright holder, namely direct payment.Keywords: Copyright, Royalty, Song/Music Users, Creator, Copyright Holder